Letter from Winnie and Tom Millham to Jane Tolmach - Winnie Millham::::::; Tom Millham:::::: (1993)
A letter from Winnie and Tom Millham thanking Jane Tolmach for her work in preventing gambling and casinos from developing in Oxnard, California.